Folic acid conjugated chitosan-based Mn(2+)-doped ZnS quantum dot for breast cancer cell imaging and targeted drug delivery - Bwatanglang, Ibrahim Birma (2017)
or the past few decades, many acquisitions were developed to unraveled cancer chemistry by designing smarter nanomaterials that can selectively target cancer cells, respond to its microenvironment and possibly support non-invasive diagnosis. However, despites the encouraging achievements in line with this concept in vitro, the use of these theranostics nanomaterials in vivo remain an unfinished business. Based on this account, a nanocomposite for targeted delivery and imaging application was developed. The rational was implemented by exploring chitosan-biopolymer based system mediated by folic acid-conjugation with affinity towards folate receptors expressed by cancer cells. The folic acid conjugated chitosan-based system was further equipped with a fluorescence imaging contrast agent (Mn:ZnS) to deliver 5-Fluororaucil anti-cancer drugs selectively into tumor-microenvironment. On the basis of these strategies, four sequential wet chemistry methods was adopted to prepare the 5-FU@FACS-Mn:ZnS nanocomposite. The as-prepared nanocomposite shows an average particle size distribution of 8.42 ± 1.79 nm and emit orange-red fluorescence at ~600nm. The strategy for the preparation involves physicochemical optimization of the nanocomposites for controlled drug release, tumor targeting specificity and bioavailability. The result was accomplished by testing and optimizing the physical properties of the materials using Fourier transform infrared, ultraviolet-visible spectroscopy, thermogravimetric analysis/differential scanning calorimetry, transmission electron microscopy, field emission scanning electron microscopy/energy dispersive X-ray, X-ray diffraction, X-ray fluorescence, X-ray photoelectron spectroscopy, fluorescence microscopy and dynamic light scattering instrumentations. The in vitro result showed that the as-synthesized 5-FU@FACS-Mn:ZnS nanocomposite when compared to the pure 5-FU anti-cancer drugs induced high level of apoptosis, selectivity and allowed fluorescence imaging in the cancer cell (MCF-7 and MDA-MB231) lines. This was evident based on the MTT cell proliferation assay, the arrest in the cell cycle and the quadrant-pattern from Annexin assay respectively. In addition to the superior anti-cancer effects demonstrated by the 5-FU@FACS-Mn:ZnS in vitro, the nanocomposite was able to reduce the tumor burden by inhibiting the tumor growth by 51 % compared to 42% induced by the pure 5-FU drugs and effectively suppress the expression of pro-inflammatory NO and MDA activity levels in the 4T1 induced mice in vivo. Furthermore, the as-synthesized 5-FU@FACS-Mn:ZnS nanocomposite in comparison to the 5-FU drugs has significantly allowed the stimulation of arsenal T-cells agents (CD3+/CD4+, CD3+/CD8+) , natural killer cells (NK 1.1/CD3+) and the anti-inflammatory cytokines (IL-2, IFN- γ), thus inhibiting cancer progression/metastasis as evident in the clonogenic assay of the lungs section. Furthermore, in comparison to the pure 5-FU drugs, the 5-FU@FACS-Mn:ZnS has markedly decreased the pathological alterations caused by the 4T1 cell lines in the liver, spleen, kidney and the lungs of the cancer induced mice. These superior anti-tumor efficacy and anti-metastasis induced by the 5-FU@FACS-Mn:ZnS nanocomposite compared to the pure 5-FU drug is due to the enhanced selectivity of the folic acid conjugation towards the folate receptors expressing cancer cells, thus mediating enhanced cellular uptake of the folate-5-FU loaded conjugate into the tumor cells as evident from the tissue-biodistribution results in the 4T1 induced mice.